PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KINERJA KERJA PT SIMATELEX MANUFACTORY BATAM - Vivin Desri Dakhi; M. Khoiri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this article is to examine wether the relate variable, namely work environment and communication, have relevant influence employee performance at PT Simatelex Manufactory Batam and work environment and communication simultaneouly affect employee performance at PT Simatelex Manufactory Batam. In this research, the formula use a descriptive quantitatve though interview and survey method, accumulate primary and secondary data and disseminate questionary to a sample of 115 employees of PT Simatelex Manufactory Batam. The measuring instrument use is a measuring instrument called the Likert scale. To verify the results of the analysis, the author use descriptive statistical methods, data quality test, influence test and hypothesis. To calculate all the data, the researcher used the statistical software SPSS 25. The results of the T test showed that the work environment variable had a significant effect on employee performance, and the communication variable had a significant effect on employee performance. While the results of the F test show the variable of the work environment and communication simultaneouly have a positive and significan effect on employee performance.